Characterization key genes of Arabidopsis seedlings in response to β-caryophyllene, eugenol using combined transcriptome and WGCN analysis - Guo, Yuqi; Liu, Chang; Zhang, Yaran; Zheng, Shuting; Cao, Ping; Wang, Xiaomin; Tian, Zengyuan (Frontiers in Plant Science, 2024)
Weeds present a significant challenge to high crop yield and quality. In our study, we investigated the phytotoxic activity of β-caryophyllene (BCP) and eugenol, which are natural allelopathic chemical compounds, on Arabidopsis seedlings. We found that these compounds inhibited the growth of Arabidopsis thaliana plants. When either BCP or eugenol was applied, it led to decrease in the content of cell wall components such as lignin, cellulose, hemicellulose, and pectin; and increase in the levels of endogenous hormones like ETH, ABA, SA, and JA in the seedlings. Through transcriptome profiling, we identified 7181 differentially expressed genes (DEGs) in the roots and shoots that were induced by BCP or eugenol. The genes involved in the synthesis of lignin, cellulose, hemicellulose, and pectin were down-regulated, whereas genes related to synthesis and signal transduction of ABA, ETH, SA, and JA were up-regulated. However, genes related to IAA synthesis and signal transduction were found to be down-regulated. Furthermore, we characterized 24 hub genes using Weighted Correlation Network Analysis (WGCNA). Among them, the identified 16 genes in response to BCP was primarily associated with hypoxia stress, while 8 genes induced by eugenol were linked to inhibition of cell division. Our results suggested that BCP and eugenol had ability to target multiple genes to inhibit growth and development of Arabidopsis plants. Therefore, they can serve as excellent candidates for natural biological herbicides.